Capabilities and competencies for digitised human resource management: perspectives from Australian HR professionals. (28th September 2022) - Nankervis, Alan R; Cameron, Roslyn
Abstract : This research aimed to identify the HR strategies and functions most likely to be affected by emerging digital technologies and explores the competencies and capabilities required by present and future HR professionals to transform these changing functions. Further, it analyses the developmental roles of educational institutions and professional associations in equipping HR professionals for this transition process. The study employed an exploratory sequential mixed methods research design incorporating two phases. Phase I involved a survey of HR professionals ( n = 203) and Phase II involved a focus group of senior HR professionals and HR academics involved in accrediting HR courses nationally in Australia. The findings point to a patchy uptake of smart technologies, artificial intelligences, robotics and algorithm (STARA) technologies in workplaces, with the expected usage of most of these technologies more likely in the future than currently. Most HR functions and HR roles are likely to be affected by these new digital technologies and associated competencies and skills.